Role of Caveolae family-related proteins in the development of breast cancer - Han, Qinyu; Qiu, Shi; Hu, Huiwen; Li, Wenjing; Li, Xiangqi (Frontiers in Molecular Biosciences, 2023)
Breast cancer has become the most significant malignant tumor threatening women's lives. Caveolae are concave pits formed by invagination of the plasma membrane that participate in many biological functions of the cell membrane, such as endocytosis, cell membrane assembly, and signal transduction. In recent years, Caveolae family-related proteins have been found to be closely related to the occurrence and development of breast cancer. The proteins associated with the Caveolae family-related include Caveolin (Cav) and Cavins. The Cav proteins include Cav-1, Cav-2 and Cav-3, among which Cav-1 has attracted the most attention as a tumor suppressor and promoting factor affecting the proliferation, apoptosis, migration, invasion and metastasis of breast cancer cells. Cav-2 also has dual functions of inhibiting and promoting cancer and can be expressed in combination with Cav-1 or play a regulatory role alone. Cav-3 has been less studied in breast cancer, and the loss of its expression can form an antitumor microenvironment. Cavins include Cavin-1, Cavin-2, Cavin-3 and Cavin-4. Cavin-1 inhibits Cav-1-induced cell membrane tubule formation, and its specific role in breast cancer remains controversial. Cavin-2 acts as a breast cancer suppressor, inhibiting breast cancer progression by blocking the transforming growth factor (TGF-β) signaling pathway. Cavin-3 plays an anticancer role in breast cancer, but its specific mechanism of action is still unclear. The relationship between Cavin-4 and breast cancer is unclear. In this paper, the role of Caveolae family-related proteins in the occurrence and development of breast cancer and their related mechanisms are discussed in detail to provide evidence supporting the further study of Caveolae family-related proteins as potential targets for the diagnosis and treatment of breast cancer.